The entrepreneurial intention of university students: An environmental perspective - Virginia Barba-Sánchez; María Mitre-Aranda; Jesús del Brío-González (European Research on Management and Business Economics, 2022)
Purpose: This paper seeks evidence of which variables, directly or indirectly, have influence on the entrepreneurial intention of university students in order to adequately plan activities to reinforce such intention for Spanish universities. Specifically, we introduce the variable of environmental awareness to test whether it induces a greater entrepreneurial intention. Study design/methodology/approach: The target population of the study has been students at the University of Oviedo who were enrolled in an undergraduate degree or a master's degree during the 2018–2019 academic year. A questionnaire has been sent obtaining the following data: 1,337 valid questionnaires, 2.58% sampling error rate for 95% confidence level, p = = q = = 0,5. To contrast the proposed hypotheses we have used the methodology of structural equations (SEM model). Findings: Starting from the Ajzen´s Theory (TPB) we demonstrate that both the attitude towards the entrepreneurial behaviour (PA) and the perceived behavioural control (PBC) exert a significant influence on the entrepreneurial intention (EI) of university students. This is not the case of the third construct of the TPB, namely the social norms (SNs). We have verified that PA partially mediates the relationship between the PBC and the EI and PA totally mediates the relationship between the PBC and the EI. We have corroborated that a high degree of environmental awareness of university student's exerts influence in their PA. Finally, it has been corroborated that the SNs which are most proactive towards entrepreneurship mediate the relationship between the student's EnvA and the PA. Originality/value: This paper proposes a variation of the model of planned behaviour (Ajzen's TPB) incorporating with the addition of mediating relationships amongst the variables and the introduction of the environmental awareness variable applied to the entrepreneurial intention of university student. The usefulness of this paper is to provide scientific evidence to support the inclusion of ecological transition in Estrategia España Nación Emprendedora.